Iron-based sulfur and nitrogen dual doped porous carbon as durable electrocatalysts for oxygen reduction reaction. (29th January 2022) - Choudhury, Fatema Akthar; Norouzi, Nazgol; Amir, Kaiynat; Demir, Muslum; El-Kaderi, Hani M.
Abstract: The widespread use of fuel cell technology is hampered by the use of expensive and scarce platinum metal in electrodes which is required to facilitate the sluggish oxygen reduction reaction (ORR). In this work, a viable synthetic approach was developed to prepare iron-based sulfur and nitrogen dual doped porous carbon (Fe@SNDC) for use in ORR. Benzimidazole, a commercially available monomer, was used as a precursor for N doped carbon and calcined with potassium thiocyanate at different temperatures to tune the pore size, nitrogen content and different types of nitrogen functionality such as pyridinic, pyrrolic and graphitic. The Fe@SNDC–950 with high surface area, optimum N content of about 5 at% and high amount of pyridinic and graphitic N displayed an onset potential and half-wave potential of 0.98 and 0.83 V vs RHE, respectively, in 0.1 M KOH solution. The catalyst also exhibits similar oxygen reduction reaction performance compared to Pt/C (20 wt%) in acidic media. Furthermore, when compared to commercially available Pt/C (20 wt%), Fe@SNDC–950 showed enhanced durability over 6 h and poison tolerance in case of methanol crossover with the concentration up to 3.0 M in oxygen saturated alkaline electrolyte. Our study demonstrates that the presence of N and S along with Fe-N moieties synergistically served as ORR active sites while the high surface area with accessible pores allowed for efficient mass transfer and interaction of oxygen molecules to the active sites contributing to the ORR activity of the catalyst. Graphical abstract: Image 1 Highlights: A viable synthetic approach was developed to prepare iron-based ORR catalyst supported on S/N-doped porous carbon. The catalyst possesses very good ORR performance comparable to that of commercial Pt/C. Fe@SNDC–950 exhibits methanol tolerance, high durability, and stability in oxygen saturated alkaline electrolyte.